MULTICULTURAL EDUCATION IN THE DIGITAL AGE: STRATEGIES FOR BUILDING DIVERSITY LITERACY IN GENERATION Z - Siti Kholida; Mujamil Qomar; Syamsun Ni’am (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The rapid development of digital technology has transformed social interaction patterns, information access, and identity formation among young people, particularly Generation Z, who have grown up in a highly dynamic digital environment. While technological advancement provides opportunities to enhance awareness of diversity, it also increases the risks of intolerance, hate speech, social polarization, and the spread of misinformation. This situation highlights the importance of multicultural education as a strategy for fostering diversity literacy and developing inclusive, tolerant, and respectful attitudes toward differences. This study aims to analyze the role of multicultural education in strengthening diversity literacy among Generation Z in the digital era and to identify effective implementation strategies within educational settings. The research employs a qualitative approach using a library research method by examining relevant books, scholarly articles, and academic documents. The findings indicate that multicultural education plays a significant role in developing critical thinking, social empathy, intercultural awareness, and responsible digital media skills. Effective strategies include integrating multicultural values into the curriculum, strengthening digital literacy, implementing collaborative learning, and utilizing technology as a medium for intercultural dialogue. These findings demonstrate that multicultural education is a strategic instrument for preparing Generation Z to live harmoniously in diverse and globally connected societies.